BRITISH ECONOMY, SPORTS AND MASS MEDIA (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the complex and symbiotic relationship  between the British economy, sports culture, and mass media, illuminating the  interconnected nature of these influential sectors. With a comprehensive overview of the diverse British economy, ranging from traditional industries to cutting-edge sectors, the piece highlights the economic significance of the sports industry, which not only generates substantial revenue but also attracts global investments and tourism. The article skillfully explores the profound impact of sports on British culture, emphasizing its role as a unifying force that transcends societal divisions. It examines iconic sporting events and the success of British athletes on the international stage, illustrating how these achievements foster a sense of national pride and contribute to the positive global image of the country. Additionally, the discussion on mass media provides valuable insights into its crucial role in shaping public perception and disseminating information. The article underscores the media's influence on sports, from reporting on events to contributing to the commercialization of sports through broadcasting rights and sponsorships. The global reach of British sports leagues and events is explored in the context of media coverage, emphasizing its impact on both the economic value of sports and the UK's soft power on the global stage